2017
DOI: 10.1177/1359105317692145
|View full text |Cite
|
Sign up to set email alerts
|

Intrasexual competition as a potential influence on anabolic-androgenic steroid use initiation

Abstract: An estimated 293,000 people living in the UK have used Anabolic-androgenic steroids.However, there is currently no intervention to reduce usage available in practice, or academic circulation throughout the UK. This study aimed to test a novel hypothesis that increased levels of intrasexual competition may play an important influential role in the use of AASs.Significantly higher levels of intrasexual competition were evident in users compared to nonusers but only in the novice group (0-2 years' experience). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 40 publications
0
9
1
Order By: Relevance
“…While we might expect these effects to be more pronounced among women (Buss & Dedden, 1990), recent research has suggested that men's use of steroids (a potential route to muscular enhancement) is also associated with intrasexual competition (Harris, Dunn, & Alwyn, 2017).…”
Section: Studymentioning
confidence: 95%
See 1 more Smart Citation
“…While we might expect these effects to be more pronounced among women (Buss & Dedden, 1990), recent research has suggested that men's use of steroids (a potential route to muscular enhancement) is also associated with intrasexual competition (Harris, Dunn, & Alwyn, 2017).…”
Section: Studymentioning
confidence: 95%
“…We chose to manipulate physical attractiveness as this is a variable that is clearly displayed in the sexually explicit images that is also linked to both intrasexual competition and rival derogation, and potentially to offense-related cognition (e.g., rape myths related to female appearance; Burt, 1980). Although we might expect these effects to be more pronounced among women (Buss & Dedden, 1990), recent research has suggested that men’s use of steroids (a potential route to muscular enhancement) is also associated with intrasexual competition (Harris et al, 2019).…”
Section: Studymentioning
confidence: 99%
“…Motives for commencement, continuation, and potential cessation of IPED use should also receive continued research attention [ 92 , 98 , 120 ]. Key examples identified for further attention include body image [ 96 , 97 , 129 ], muscle dysmorphia [ 94 ], muscularity [ 82 ], masculinity [ 87 , 130 ], and hypogonadism [ 99 , 113 , 115 ].…”
Section: Discussionmentioning
confidence: 99%
“…We chose to manipulate physical attractiveness as this is a variable that is clearly displayed in the sexually-explicit images that is also linked to both intrasexual competition and rival derogation, and potentially to offence-related cognition (e.g., rape myths related to female appearance; Burt, 1980). While we might expect these effects to be more pronounced among women (Buss & Dedden, 1990), recent research has suggested that men's use of steroids (a potential route to muscular enhancement) is also associated with intrasexual competition (Harris, Dunn, & Alwyn, 2017).…”
Section: Studymentioning
confidence: 94%